Optimalisasi Pendayagunaan Zakat Melalui Program Beasiswa Prestasi Tahun 2017-2020: - Atika Suri; Annio Indah Lestari Nasution; Nursantri Yanti, (ManBiz: Journal of Management and Business, 2024)
This study was conducted to determine whether the utilization of zakat carried out by Dompet Dhuafa Waspada (DDW) in collaboration with UPZ Bank SUMUT through0the achievement scholarship program has been running optimally or not. The0purpose of this study is to find0out how the zakat utilization mechanism is applied by DDW, especially in the merit scholarship program in the Dompet Dhuafa Waspada2 North Sumatra, and to find out how the impact of awarding merit scholarships has on increasing the entrepreneurial desire of the scholarship beneficiaries which leads to the conclusion whether the utilization of scholarships is beneficial. What is done by the underprivileged wallet is alert that it is optimal or not optimal. This study use a descriptive approach0with the type of research is qualitative, so0the data analysis used is0descriptive qualitative0analysis. The results of this study indicate that the achievement scholarship program run by DDW in collaboration with UPZ Bank SUMUT has been running optimally. It is evident from the amount of funds obtained since 2017-2020 which has increased, as well as all the efforts they have made to make this program better and more effective. Then this achievement scholarship program has also resulted in significant changes to the lives of the scholarship beneficiaries, starting from the assistance in education costs, increasing skills and knowledge about entrepreneurship. However, there is still a need for further improvements in the implementation of this program so that this program continues to improve and be more optimal. Keywords: Utilization of zakat, Achievement Scholarship, optimization